Solitary confinement: From religious espiatio to its incapacitating secularization (Delito y Sociedad, 2021)
Where does the idea of isolating people deprived of freedom come from? Why was it even decided to isolate people in order to deprive them of freedom? Why is solitary confinement still used today? These are some of the questions that this article will answer. Through a genealogy approach to solitary confinement, this article explores the features of isolation in the early stages of the history of confinement and during the reception phase of the prison systems in Europe (in particular in Spain). It does so in order to better understand its discipline and purpose within the prison system in Spain and Catalonia. If at first solitary confinement was intended to achieve the moral reform of the prisoner through the penitential espiatio, solitary confinement gradually became the main disciplinary technique to achieve the submission of the prisoner to power and authority, as well as setting itself up as the preeminent practice to incapacitate and neutralize the «dangerous» ones.
Keywords: solitary Confinement; prison System; prison History; genealogy; spain